TERT promotor status does not add prognostic information in IDH-wildtype glioblastomas fulfilling other diagnostic WHO criteria: A report of the RANO resect group - Karschnia, Philipp; Young, Jacob S.; Dono, Antonio; Häni, Levin; Juenger, Stephanie T.; Sciortino, Tommaso; Bruno, Francesco; Teske, Nico; Morshed, Ramin A.; Haddad, Alexander F.; Zhang, Yalan; Stoecklein, Sophia; et al. (Neuro-Oncology Advances, 2022)
In IDH-wildtype glioblastomas which meet the histopathological or molecular diagnosis criteria, it remains unclear whether the presence of TERT promotor mutations provides additional prognostic information. Based on a multicenter cohort of 466 IDH-wildtype glioblastomas (including 396 with and 70 patients without TERT promotor mutations), we found that TERT promotor mutations were neither associated with progression-free survival nor overall survival. This held true in various treatment-based or molecular subgroups. This argues against standardized analysis for TERT promotor mutation status for the purpose of prognostic or therapeutic relevance in newly diagnosed IDH-wildtype glioblastoma that otherwise meets the histopathological and molecular diagnosis criteria.
CRIS-Team Scopus Importer:2023-09-13